Maternal and neonatal outcomes in triplet gestations by trial of labor versus planned cesarean delivery - PERESS, Danielle (J Matern Fetal Neonatal Med, 2018)
OBJECTIVE: To determine the rate of vaginal delivery after vaginal trial of labor (TOL) among women with triplet gestations. STUDY DESIGN: This is a retrospective cohort study of all women delivering a viable triplet gestation between 2005–16. The primary outcome was rate of vaginal delivery among all women attempting vaginal delivery. Secondary outcomes included factors associated with undergoing triplet TOL and maternal and neonatal complications by planned delivery approach. RESULTS: Of 83 eligible women, 21 (25.3%) underwent TOL. A majority of these (57.1%, 95% confidence interval 36.5% - 75.5%) achieved a vaginal delivery of all three triplets. Women who underwent TOL were more likely to be multiparous or to have spontaneous preterm labor. There were no differences in adverse maternal or neonatal outcomes by planned delivery approach. CONCLUSION: The rate of vaginal delivery among women with triplet gestations is higher in this institution than in reported literature, without increased morbidity.